(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This article aims to shed light on the impact of AI in general and big data in particular on financial inclusion in the context of FinTech companies. Using a literature review based on articles of high scientific value and significant influence on the academic debate in research on the topic, we found that in the context of FinTech companies, big data represents a key tool to properly segment the market and provide more personalized and less expensive financial services by analyzing consumers’ activities on various sites on intranet pages. It also helps FinTech companies analyze customer transaction data not only to assess their creditworthiness and reliability as customers, but also to offer more personalized and less expensive products and services that promote financial inclusion. The use of big data analytics provides the opportunity for financial service providers to reach a larger base of beneficiaries who have been excluded by traditional financial service providers, creating more efficient and effective economic models.